PERANCANGAN SISTEM INFORMASI AKADEMIK ONLINE MENGGUNAKAN BLACK BOX TESTING PADA SEKOLAH TINGGI ILMU EKONOMI SURYA NUSANTARA - Harmonvikler Dumoharis Lumbanraja (TeIKa, 2018)
Making of Academic Information System of Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, Pematangsiantar uses a structured approach, while the method of development using prototype with designing technique that was preceded by the collection of observation data and interviews are classified in the Waterfall method stages. While the tools used in designing the system form Use Case Diagrams, HTML, PHP, Javascript, CSS and use some software such as XAMPP, Browser, StarUML, Sublime Text 3, Notepad + +. The testing of this system using Black box testing, where this type of testing is considered the most appropriate to represent the use of menus are made. The built system is presented on a client server so that it can be accessed by all users of lecturers and students. The system built is expected to overcome most of the existing problems such as reporting the value of students online, online registration form input KRS online. Online academic information system is expected to continue to be developed to handle every need in academic administration bureau of Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, Pematangsiantar.